2014
DOI: 10.2471/blt.14.143917
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of adults seeking emergency care in Cambodia

Abstract: ObjectiveTo describe the characteristics and chief complaints of adults seeking emergency care at two Cambodian provincial referral hospitals.MethodsAdults aged 18 years or older who presented without an appointment at two public referral hospitals were enrolled in an observational study. Clinical and demographic data were collected and factors associated with hospital admission were identified. Patients were followed up 48 hours and 14 days after presentation.FindingsIn total, 1295 hospital presentations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 10 publications
1
18
1
Order By: Relevance
“…Fourth, the course content was tailored to the most likely scenarios the providers would face, based on existing data on patterns of emergency presentations and referrals [ 16 ]. With obstetric and peripartum conditions comprising a large portion of hospital presentations in Cambodia, maternal and pediatric emergencies were given more attention in this curriculum than in most prehospital care provider training curriculums from more developed EMS systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, the course content was tailored to the most likely scenarios the providers would face, based on existing data on patterns of emergency presentations and referrals [ 16 ]. With obstetric and peripartum conditions comprising a large portion of hospital presentations in Cambodia, maternal and pediatric emergencies were given more attention in this curriculum than in most prehospital care provider training curriculums from more developed EMS systems.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulances are mostly controlled by and stationed at the government referral hospitals with limited coordination occurring between facilities. Consequently, patients with emergency conditions most commonly arrive at health facilities via private vehicle, motorbike, taxi, or tuk-tuk (a passenger carrying cart pulled by a motorcycle) [ 16 ]. Research on interfacility transfer (IFT) for emergency obstetric and neonatal care (EmONC) has shown that nearly half of patients being referred are required to arrange their own transportation.…”
Section: Technical Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, few if any Cambodian hospitals have systems in place to assist in identifying and prioritizing ill patients as they arrive. 10 At many facilities, patients self-triage to the hospital department they deem most appropriate (eg, emergency department, intensive care unit, inpatient wards), where they are cared for in the order of arrival, delaying the care of critically ill patients and leading to worsened outcomes. With this in mind, as part of the project's efforts, a simple Cambodiaspecific triage system was designed and implemented at 35 referral hospitals.…”
Section: Variable Recognition Of Emergency Conditionsmentioning
confidence: 99%
“…Going further, unfortunately, many Cambodian healthcare providers lack adequate emergency-specific skills and training, and as a result often fail to utilize the tools required to recognize and manage complex obstetric, pediatric, and general emergencies. 10 Due to the limited supply of specialists and facilities with the capacity to care for life-threatening conditions, emergent patient referrals are often imperative. However, the Cambodian emergency referral system is difficult to navigate and inconsistently available.…”
mentioning
confidence: 99%